2020
DOI: 10.1146/annurev-food-032519-051827
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Human Health: What Is the Evidence?

Abstract: Alcohol consumption has long been a part of human culture. However, alcohol consumption levels and alcohol consumption patterns are associated with chronic diseases. Overall, light and moderate alcohol consumption (up to 14 g per day for women and up to 28 g per day for men) may be associated with reduced mortality risk, mainly due to reduced risks for cardiovascular disease and type-2 diabetes. However, chronic heavy alcohol consumption and alcohol abuse lead to alcohol-use disorder, which results in physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 140 publications
1
54
0
8
Order By: Relevance
“…These categories include: (1) long‐term abstinence from alcohol (LA); (2) binge drinking (BD), intake of an excessive, large amount of alcohol over a short period of time (within a 2‐h time period on one occasion) with no intention to stop drinking (two to three times per month with ≥4 and 5 drinks for females and males, respectively); (3) long‐term damaging alcohol drinking that exceeds the safe drinking dosage recommend by WHO (LD), with alcohol intake of <4 to ≥3 drinks and <5 to ≥4 drinks per day for females and males, respectively; (4) long‐term low dosage drinking, involving the consumption maximum two drinks of alcohol per day for both females and males (LDD); and (5) long‐term heavy drinking (HD), alcohol intake ≥5 drinks per day, regardless of sex. Previous studies reported that alcohol‐drinking patterns are associated with different risks to ARBD, physiological alcohol‐related diseases, financial burdens of ARBD (Esser et al., 2020; Hendriks, 2020; Liu, 2020; Silveira et al., 2020). Drinking alcohol impairs specific brain regions, including the occipital lobe, parietal lobe, frontal cortex, temporal lobe, cingulate cortex, and thalamus.…”
Section: Introductionmentioning
confidence: 99%
“…These categories include: (1) long‐term abstinence from alcohol (LA); (2) binge drinking (BD), intake of an excessive, large amount of alcohol over a short period of time (within a 2‐h time period on one occasion) with no intention to stop drinking (two to three times per month with ≥4 and 5 drinks for females and males, respectively); (3) long‐term damaging alcohol drinking that exceeds the safe drinking dosage recommend by WHO (LD), with alcohol intake of <4 to ≥3 drinks and <5 to ≥4 drinks per day for females and males, respectively; (4) long‐term low dosage drinking, involving the consumption maximum two drinks of alcohol per day for both females and males (LDD); and (5) long‐term heavy drinking (HD), alcohol intake ≥5 drinks per day, regardless of sex. Previous studies reported that alcohol‐drinking patterns are associated with different risks to ARBD, physiological alcohol‐related diseases, financial burdens of ARBD (Esser et al., 2020; Hendriks, 2020; Liu, 2020; Silveira et al., 2020). Drinking alcohol impairs specific brain regions, including the occipital lobe, parietal lobe, frontal cortex, temporal lobe, cingulate cortex, and thalamus.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies not only point to the mechanism of protection ( Brien et al ., 2011 ), but also indicate that the mechanism is very similar when consuming wine, beer or spirits. Main effect of moderate alcohol consumption appears to be the inhibition of the atherosclerotic process ( Hendriks, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term excessive drinking and binge drinking also result in many negative health effects. However, short-term and long-term light to moderate alcohol consumption have been associated with several positive health outcomes ( Hendriks, 2020 ). Consequently, many countries have guidelines advising low to moderate alcohol consumption aimed at reducing the health burden caused by the misuse of alcohol ( WHO, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, alcohol also possesses both toxic and intoxicating properties. Alcohol is a toxic substance that is foreign to the body (not produced by the body), and it can lead to serious poisonous effects, especially when taken in high concentrations [4]. In general, the harmfulness of alcohol consumption can be related to the total volume of irregular heavy drinking [5,6].…”
Section: Introductionmentioning
confidence: 99%